2018
DOI: 10.1016/j.anai.2018.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal lung function at preschool age asthma in adolescence?

Abstract: Abnormal preschool IOS is associated with asthma and poor lung function in adolescence and might be utilised for identification of asthma persistence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 34 publications
0
36
0
1
Order By: Relevance
“…Instead, IOS alone showed good potential as a screening method for persistent asthma with connection to both objective and subjective signs. These prognostic features of baseline R5 and X5 (both representatives of small airways) were further elucidated when compared to our previous study, when these features were evaluated with a control group 11 . However, the predictive value of IOS parameters and hypertonic saline are more indicative than conclusive and further studies are necessary.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Instead, IOS alone showed good potential as a screening method for persistent asthma with connection to both objective and subjective signs. These prognostic features of baseline R5 and X5 (both representatives of small airways) were further elucidated when compared to our previous study, when these features were evaluated with a control group 11 . However, the predictive value of IOS parameters and hypertonic saline are more indicative than conclusive and further studies are necessary.…”
Section: Discussionmentioning
confidence: 80%
“…IOS was combined with an outdoor exercise challenge test and a bronchodilator test. The entry criteria included either increase of ≥ 35% in resistance at 5 Hz (R5) after exercise challenge or a decrease of ≥ 35% in R5 after bronchodilation test 11 . At this age, AHR was also estimated with a bronchial challenge test with hypertonic saline.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, positive API preschoolers with ICS had significantly higher central basal airway resistance (RA at 20 Hz) and higher post-BD response (% change in FEF 25−75 and FEV 0.5 ) than those positive API without ICS; suggesting that preschoolers with positive API and ICS use may have some airway dysfunction (49). Recently, a Finish longitudinal study (50) about lung function assessed with IOS measured at preschool age ( n = 255) and at adolescence, showed that abnormal baseline values (poor R5) during preschool were significantly associated with: low lung function, need for asthma medication, and asthma symptoms during adolescence. And a positive API at preschool age was associated with asthma symptoms (OR: 13.7 [1.4–147.1]) and need for asthma medication (OR: 14.6 [1.4–147.1]), but not with abnormal lung function at adolescence (50).…”
Section: Predictive Models For Prognostic or Diagnostic Toolsmentioning
confidence: 99%
“…Studies in children are very limited in this regard. One study has noted that in children between the ages of 3 and 8 years old, a change in the R5/R20 after methacholine challenge was significantly higher in those children with more severe asthma as shown by increased exercise-induced bronchospasm and short-acting beta 2 agonist use [11].…”
Section: Ios and Airway Hyperreactivitymentioning
confidence: 99%